PERANCANGAN SISTEM INFORMASI ADMINISTRASI KEUANGAN MENGGUNAKAN METODE CASH BASIS PADA ORGANISASI NIRLABA - Ahmad Ashifuddin Aqham; Tiara Ayu Marensa; Sukemi Kamto Sudibyo; Bagus Sudirman (Lembaga Pengembangan Kinerja Dosen, 2022)
GKJTU Kendal in managing its financial administration is still manually, namely by writing in a handwritten book. The progressive growth of the number of congregations in GKJTU Kendal has certainly resulted in significant data growth. This results in the treasurer having difficulty in processing financial statements. The purpose of this study is to produce a church financial administration information system using the cash basis method to be applied to the GKJTU Kendal to assist the assembly in the process of managing financial reports to be more effective and computerized. The design and development of this information system uses the PHP programming language, Sublime Text 3 as a text editor, MySQL as a database, with Research and Development research methods. With this system, it is hoped that it will facilitate the process of managing financial administration at GKJTU Kendal, so that financial reporting can be more transparent and the congregation can also trust the assembly who manages finances more. This system can process financial administration more quickly, easily, and effectively in data processing. The existence of a website-based financial administration information system is the best solution to overcome the problems that exist in GKJTU Kendal.